Legal Review of the Policy on the Use of Artificial Intelligence in the Judicial System in Indonesia - Amiroel Oemara Syarief; Merina Pratiwi (Asosiasi Dosen Muda Indonesia, 2025)
The use of artificial intelligence (AI) in legal practice is increasingly growing, particularly in legal precedent research and the drafting of court documents. This study employs a normative juridical approach and aims to examine the legal aspects of a specific case, focusing on the professional responsibility of lawyers, procedural law provisions, and the impact on the integrity of the judicial system. The findings indicate that although AI enhances efficiency, its use without human verification can undermine legal credibility and lead to ethical and legal sanctions for practitioners.